Analisis Perbandingan Konsep Nilai Tukar dalam Ekonomi Konvensional dan Islam serta Implikasinya terhadap Stabilitas Ekonomi - Dewi Jannati Asih Putri; M. Rafiudin Safikri; Puja Audinia Artika; Suci Hayati (Teewan Journal Solutions, 2025)
Currency exchange rates are important for many economic activities, including capital flows, international trade, and investment. These activities have an impact on the competitiveness of domestic goods, the welfare of individuals, and the stability of the economy as a whole. The economic system in use determines how exchange rates are handled. The notion of exchange rates in conventional and Islamic economics, as well as its effects on economic stability, are examined in this study using a qualitative approach and a literature study methodology. Descriptive analysis is performed on secondary data gathered from different literature sources and fatwas. The results demonstrate that, in order to lower the risk of exchange rate volatility, the Islamic economy places a strong emphasis on the values of justice, the prohibition of usury, and transparent cash transactions. In contrast, the conventional economic system depends on market mechanisms and interest rate-based monetary policies that are susceptible to fluctuations and speculation. More socially just and durable stability may be possible with this Islamic economic strategy. Consequently, using Islamic economic concepts to manage exchange rates can be a useful substitute for preserving the stability of the national economy.